Stochastic analysis of human factor in information model of labor protection system management - Матиборский, В. В. (Proceedings of National Aviation University (archive), 2000)
Demonstrated is the possibility of application of stochastic analysis of human imitation model in the labor protection management system, also the possibility of finding response of such model on influence of stochastic dangerous and harmful industrial factors